Unmanned Aerial Vehicle Design for Application in Cyber Security - Gambaryan, M. K.
In this paper a small copter size unmanned aerial Vehicle (UAV) has been designed as a platform for a flying computer station to carry out cyber-attacks (Jamming, Spoofing, Man in the Middle, etc.) on devices that utilize wireless technologies, WiFi in particular. A yagi-patch hybrid antenna designed for 2.4 GHz freely rotates on two axes, thus allowing the drone to perform attacks on low power devices up to ranges of 300 meters. The modular design of the UAV allows for quick swapping of modules depending on the specific wireless technology used by the target device.
Keywords: Physics